Pregnancy Outcomes Following GnRH- or Prostaglandin-Based Timed Artificial Insemination Protocols in Water Buffaloes (Bubalus bubalis) - Atabay, E.C.; Atabay, E.P.; Cruz, C.F. Dela; Ferrer, A.V. (Journal of Buffalo Science, 2024)
The efficiencies of Timed Artificial Insemination (TAI) protocols in post-partum riverine dairy buffaloes were evaluated in the present research work. In Study 1, GnRH-based ovulation synchronization for Fixed Time Artificial Insemination (FTAI) protocol was evaluated for pregnancy. Buffaloes in Treatment 1 were subjected to the Ovsynch (GnRH-PGF2α-GnRH) protocol. Buffaloes in Treatment 2 were subjected to Controlled Internal Drug Release–Gonadotrophin Releasing Hormone (CIDR-Synch-GnRH) protocol, and buffaloes in Treatment 3 were subjected to CIDR-Synch-human Chorionic Gonadotrophin (CIDR-Synch-hCG) protocol. In Study 2, Prostaglandin-based estrus synchronization protocols were similarly evaluated for pregnancy. Buffaloes in Treatment 1 were treated with Prostaglandin hormone alone; buffaloes in Treatment 2 were subjected to Prostaglandin-GnRH protocol, while buffaloes in Treatment 3 were subjected to Prostaglandin-hCG protocol. Results in Study 1 revealed that supplementation of Ovsynch with CIDR in Treatment 2 and 3 resulted in significantly higher (P<0.05) pregnancy rates compared with Ovsynch alone (T1). Meanwhile, the use of hCG as the final ovulatory hormone in FTAI protocol (T3) yielded a significantly higher (P<0.05) pregnancy rate than GnRH (T2). In Study 2, results showed that prostaglandin protocols enhanced with GnRH (T2) or with hCG (T3) resulted in significantly higher (P<0.05) pregnancy rates (31.88±3.39 and 34.62±1.53), respectively, compared with Prostaglandin alone (T1, 23.91±2.49). However, pregnancy rates in Prostaglandin-based protocols (T2) and (T3) were not significantly different (P<0.05). In sum, the present study demonstrated that supplementation with exogenous progesterone (CIDR) improved the efficiency of Ovsynch FTAI protocol while using hCG as the final ovulatory hormone is found to be the best among FTAI protocols. Meanwhile, a Prostaglandin-based protocol enhanced with ovulatory hormones, either GnRH or hCG, on the day of AI improved pregnancy rates in post-partum water buffaloes.